Hubungan Postur Kerja dengan Keluhan Musculoskeletal Disorders pada Pekerja Pabrik Tahu X di Banyuwangi Tahun 2023 - Kurniawati, Arsifa Tri; Dwiyanti, Endang; Ningtiyas, Shinta Feby; Alfayad, Afan (Media Gizi Kesmas, 2024)
Background: Humans are an important factor in the work system. Work posture in workers will determine the work productivity of workers. Tofu factories include work in the informal sector. In the production process, there are risks that can cause occupational accidents or occupational diseases in workers. One of the health risks that can occur is Musculoskeletal Disorder (MSDs) complaints due to incorrect work postures. Objective: Analyzing the relationship between work posture and pain complaints in workers who are not ergonomic when working at one of the X tofu factories in Banyuwangi, especially in the position of boiling soybean porridge. Methods: Data collection was obtained through interviews and observations. The method used in analyzing data is the Ovako Working Analysis System (OWAS) to analyze work postures in workers and the Nordic Body Map (NBM) to analyze pain complaints in workers. Data analysis was carried out using the contingency coefficient test. Result: Based on the results of the analysis, it was found that the posture of workers was not ergonomic at work, so it was a health risk. The results of the contingency coefficient statistical test analysis show that there is a strong relationship between work posture and musculoskeletal disorder (MSD) complaints. Conclusion: There is a strong relationship between work posture and Musculoskeletal Disorders (MSD) complaints among Tofu Factory X workers in Banyuwangi, so control efforts are needed so that workers experience increased work productivity and companies also get increased profits.